Chitin, Chitosan, and Glycated Chitosan Regulate Immune Responses: The Novel Adjuvants for Cancer Vaccine. (4th March 2013) - Li, Xiaosong; Min, Min; Du, Nan; Gu, Ying; Hode, Tomas; Naylor, Mark; Chen, Dianjun; Nordquist, Robert E.; Chen, Wei R.
Abstract : With the development of cancer immunotherapy, cancer vaccine has become a novel modality for cancer treatment, and the important role of adjuvant has been realized recently. Chitin, chitosan, and their derivatives have shown their advantages as adjuvants for cancer vaccine. In this paper, the adjuvant properties of chitin and chitosan were discussed, and some detailed information about glycated chitosan and chitosan nanoparticles was also presented to illustrate the trend for future development.